The Impact of AI Usage on Transforming Student Learning Culture in Indonesia in Alignment with SDG 4 - Kharis, M.; ., Ediyanto; Wijaya, Daya Negri; Yafie, Evania; Waluyo, Bagus; Resultay, Razeale G. (Journal of Ecohumanism, 2024)
This research examines the transformative effects of AI on the learning culture of university students in Indonesia, contextualized within the goals of SDG 4 for quality education. Surveying 230 students across nine faculties, including arts, business, law, and sciences, the study uses questionnaires and interviews to understand AI’s influence on students’ learning behaviors and academic efficiency. Results indicate that AI enhances self-confidence, learning speed, and effectiveness, with students reporting that AI reduces time spent on academic research and improves task efficiency. However, the integration of AI also raises concerns about academic integrity and critical thinking. This shift toward AI-assisted learning encourages autonomy but requires careful monitoring to maintain academic rigor. As AI reshapes student priorities and influences learning habits, ongoing research and adaptive teaching methods are crucial to harness AI’s full potential in fostering an equitable, effective, and responsible learning environment.